The spectrum of fibroelastolytic papulosis: a retrospective case series. - Cunha, Nélia (2018)
Introduction: There is an overlap between clinical and pathological features of the entities known as pseudoxanthoma elasticum-like papillary dermal elastolysis (PXE-PDE) and white fibrous papulosis of the neck (WFPN). Although the term fibroelastolytic papulosis has been used to encompass both entities as spectrum variants of a one and only disease, many authors still differentiate the two.Methods: Cases of fibroelastolytic papulosis confirmed by histopathologic examination were retrospectively reviewed within a time frame of 2.5 years.Results: Five cases of fibroelastolytic papulosis were identified. All patients were females aged between 63 and 78 years, presenting with an asymptomatic eruption of isolated or coalescing white to yellow papules on the neck. Two of the patients also had involvement of other anatomical areas. In all cases histology demonstrated a significantly decreased or absent papillary dermal elastic plexus, a mild superficial perivascular lymphocytic infiltrate and sparse melanophages in the papillary dermis, without interface changes. A decrease in upper reticular dermal elastic fibers was noted in four cases and thickening of dermal collagen bundles in three cases. Dilated superficial dermal vessels were present in 3 cases and mild epidermal atrophy in one case.Conclusion: We find the differentiation of PXE-PDE and WFPN to be somewhat theoretical, often confusing, and based on non-significant subtle histological and clinical differences. In our opinion, we should not continue to use these terms, but favor the common term of fibroelastolytic papulosis.